The Synchronization of N Cascade-Coupled Chaotic Systems. (12th December 2019) - Li, Pengyu; Du, Juan; Li, Shouliang; Zheng, Yazhao; Jia, Bowen
Abstract : In this paper, we investigate a novel synchronization method, which consists of n n ≥ 2 cascade-coupled chaotic systems. Furthermore, as the number of chaotic systems decreases from n to 2, the proposed synchronization will transform into bidirectional coupling synchronization. Based on Lyapunov stability theory, a general criterion is proposed for choosing the appropriate coupling parameters to ensure cascading synchronization. Moreover, 4 Lü systems are taken as an example and the corresponding numerical simulations demonstrate the effectiveness of our idea.